Injection of nanosized CO2 droplets as a technique for stable geological sequestration. (February 2016) - Uemura, Suguru; Matsui, Yohei; Kondo, Fumiya; Tsushima, Shohji; Hirai, Shuichiro
Highlights: We propose a new technique for geological sequestration using nanosized CO2 droplets. The growth rate of the droplets depends strongly on temperature and CO2 density. The resulting microscale CO2 droplets can be trapped in a porous silica medium. Surfactant properties, cost and energy use are examined as issues for implementation. Abstract: Geological sequestration of carbon dioxide (CO2 ) is considered an important technology to achieve a substantial reduction in CO2 emissions. However, leakage is a risk of geological sequestration because CO2 migrates upwards by buoyancy. This study proposes a new technique using nanosized CO2 droplets injected into a porous structure to decrease the buoyancy effect, thereby preventing the upward migration of CO2 . We focus on the formation of nanosized CO2 droplets, their subsequent size variation over time, and their behavior in porous media. Experiments are performed using a volume ratio of CO2 to water of 1:1 and trisiloxane (0.4–1.6%) as a surfactant. In the experiments, nanosized CO2 droplets with initial diameters in the range of 20–100 nm are successfully generated. The droplet coalescence rate depends on both temperature and CO2 density. Experimental results also indicate that sufficiently small CO2 droplets can be maintained throughout the injection process and readily introduced into an aquifer. Microfocus X-ray computed tomography shows that CO2 is stably trapped in a porous medium. This study suggests that nanosized CO2 droplets hold considerable promise as a means of stable geological sequestration. Surfactant optimization and cost reduction need to be addressed for field application of this approach.